The long-term prognostic implications of free triiodothyronine to free thyroxine ratio in patients with obstructive sleep apnea and acute coronary syndrome - Zhou, Yun; He, Qian; Ai, Hui; Zhao, Xuedong; Chen, Xiuhuan; Li, Siyi; Zhang, Zekun; Fan, Jingyao; Gong, Wei; Nie, Shaoping (Frontiers in Endocrinology, 2024)
Objective Obstructive sleep apnea (OSA) and thyroid dysfunction frequently overlap clinically and are risk factors for cardiovascular disease. The free triiodothyronine to free thyroxine (FT3/FT4) ratio as a novel biomarker of cardiovascular disease prognosis, but the impact of the FT3/FT4 ratio on the prognosis of OSA in patients with acute coronary syndromes (ACS) remains uncertain. Methods In this prospective cohort study, 2160 patients with ACS were recruited and underwent portable sleep monitoring at Beijing Anzhen Hospital from June 2015 to January 2020. OSA was diagnosed when apnea-hypopnea index of ≥15 events/h. Patients were further divided into tertiles according to FT3/FT4 ratio. All patients had scheduled follow-up visits at 1, 3, 6, 9 and 12 months after discharge, with subsequent outpatient visits or telephone follow-up visits every 6 months. The primary endpoint was major adverse cardiovascular and cerebrovascular events (MACCE), including cardiovascular death, myocardial infarction (MI), stroke, ischemia-driven revascularization, or hospitalization for unstable angina or heart failure. Results Among 1,547 euthyroid patients enrolled (mean age, 56.0 ± 10.5 years), 812 patients (52.5%) had OSA. The FT3/FT4 ratio between OSA and non-OSA patients was not significantly different. During 2.8 (1.4, 3.5) years follow up, the risk of MACCE increased with the decreasing FT3/FT4 tertiles in patients with OSA (tertile3 as reference, tertile2: hazard ratio (HR) 1.26, 95% CI: 0.85-1.86, P = 0.255; tertile1: 1.60, 95% CI 1.11-2.32; P = 0.013). After adjustment for confounders, the lowest FT3/FT4 tertile was still independently associated with an increased risk of MACCE (adjusted HR 1.66, 95% CI 1.11-2.50, P = 0.015). Conclusion Lower FT3/FT4 ratio associated with poor prognosis in patients with ACS and OSA.